Accounting for tangible heritage asset: the case of the National Archives of Malaysia / Mohamad Hafiz Rosli and Amrizah Kamaluddin - Rosli, Mohamad Hafiz; Kamaluddin, Amrizah (UiTM Press, 2024)
The reporting of heritage assets (HA) has become relevant since the implementation of accrual accounting in the Malaysian public sector. The current disclosure requirements may not adequately capture HA significance and rarity. The research aimed to describe the issues and challenges faced in accounting for HA in line with the implementation of accrual accounting in the public sector. The study employed a qualitative approach, through face-to-face interviews with accountants and curator officers in a selected government department. The findings highlighted five emerging issues and challenges in reporting for HA including reporting issues, legislation, lack of accounting policies and reporting guidelines, expertise in the valuation of HA, and staff competency. Despite these issues and challenges, this entity had already reported its HA and has taken various initiatives to address the issues. This study contributes to the existing literature on HA accounting in Malaysia and supports the public accountability paradigm. Additionally, it provides input for policymakers and preparers to better prepare for HA reporting. While this study focussed on a single entity, future research could encompass additional government agencies for a comprehensive understanding of their reporting practices.